Indoor Environment Health and Safety Status in Industrial Sectors of Bangladesh: a Case Study on Industries under Kumudini Welfare Trust - Hoque, MMM; Banik, PK (Journal of Environmental Science and Natural Resources, 2018)
This study was conducted to know the indoor environment, health and safety status towards the workers of different industries situated in Narayanganj under Kumudini Welfare Trust (KWT) of Bangladesh. The data were collected during the monthof March-April, 2016. Measurednoise level in different industries under KWT ranged from 71-90.5 dB. During the study, among all of the four industries highest level of noise was measured in Kumudini Jute Bailing and Warehouse Ltd. (90.5 dB) followed by Kumudini Garments Ltd. (78 dB). Indoor temperature in different industries under KWT ranged from 26.5°C-32°C. Highest level of temperature was measured in Kumudini Garments Ltd. (32°C) followed by Kumudini Handicraft Ltd. (30.5°C), Kumudini Pharma Ltd. (29.5°C) and Kumudini Jute Bailing and Warehouse Ltd. (26.5°C). During the observations, highest relative humidity was measured in Kumudini Garments Ltd. (19.5%) followed by Kumudini Pharma Ltd. (5.2%), Kumudini Handicraft Ltd. (2%) and Kumudini Jute Bailing and Warehouse Ltd. (1.2%). In this study, observed level of CO2 in the indoor environment of the study area ranged from - 0.2 to 0.45 %. All of the measured CO2 level is greater than standard concentration of 0.03%, except Kumudni Jute Bailing and Ware House. Based on our present clarifications there was no oxygen deficiency in the door environment of the industries under KWT. J. Environ. Sci. & Natural Resources, 10(2): 65-72 2017